Role of the immune system and possible mechanisms in COVID-19 vaccine-induced thyroiditis: Case report and literature review - Vahid Reisi-Vanani; Mahour Farzan; Mahan Farzan; Hosein Ataei-Goujani; Maryam Keihani; Golshan Taghipour-Boroujeni (Journal of Clinical and Translational Endocrinology Case Reports, 2022)
Introduction: Subacute thyroiditis (SAT) is an inflammatory disease that has different trigger factors. Recent studies show the possible role of COVID-19 vaccine-induced thyroiditis in its initiation. Herein we report the first case of post-Sputnik V vaccination SAT. Case presentation: A 42-year-old man without any specific disease was admitted due to tremors, palpation and sweating, and neck tenderness on the thyroid gland. Laboratory markers and radiologic assessments highlighted thyroiditis for him, and his symptoms were relieved by administering NSAIDs and corticosteroids. Discussion: There are several hypotheses for the etiology of post-COVID-19 immunization SAT; among them, immunologic reactions like the interactivity of human proteome with viral components and autoimmune/inflammatory syndrome induced by adjuvants (ASIA) are more probable than other discussed possibilities. We suggest further studies to discover the exact SAT pathophysiology to prevent the underlying causes among future vaccine candidates.